Prediction of Anaerobic Power From Standing Long Jump in NCAA Division IA Football Players. Issue 6 (June 2021) - Mann, J. Bryan; Bird, Michael; Signorile, Joseph F.; Brechue, William F.; Mayhew, Jerry L.
Abstract : Abstract: Mann, JB, Bird, M, Signorile, JF, Brechue, WF, and Mayhew, JL. Prediction of anaerobic power from standing long jump in NCAA Division IA football players. J Strength Cond Res 35(6): 1542–1546, 2021—Despite the popularity of the standing long jump (SLJ), limited research has explored the estimation of power developed during this test. The purpose of this study was to determine SLJ power from jump distance and selected anthropometric measures in NCAA Division IA football players. Height (Ht), body mass (Wt), thigh length, and lower leg length (LL) were measured in 58 players, allowing calculation of leg ratios of thigh length·Ht −1, LL·Ht −1, and TL·SL −1 . Players performed 2–3 maximal familiarization trials of SLJ followed by 2 maximal jumps from a 3-dimension force plate sampling at 1, 000 Hz. Standing long jump distance (intraclass correlation coefficient [ICC] = 0.944) and power (ICC = 0.926) calculated from resultant force and velocity vectors were highly reliable. Standing Ht ( r = 0.40), Wt ( r = 0.36), lower leg length ( r = 0.43), total leg length (thigh + LLs) ( r = 0.38), and best SLJ ( r = 0.52) were significantly related ( p < 0.05) to peak power, but none accounted for more than 27% of the common variance. Step-wise multiple regression identified SLJ and body mass as the only significant variables necessary to predict peak power (Power [W] = 32.49·SLJ [cm] + 39.69·Wt [kg] − 7, 608, R = 0.86, SEE = 488 W, CV% = 9.3%). Standing long jump contributed 56.8% to the known variance, whereas Wt contributed 43.2%. Thus, a combination of SLJ and Wt can be used to effectively estimate explosive power in Division IA college football players.